Usos do conceito de eventos privados à luz de proposições pragmatistas - VASCONCELOS NETO, Aécio de Borba (2011)
Uses of the concept of private events from the standpoint of pragmatist assumptions. The concept of private events has been used in behavior-analytic literature as a major topic to the treatment phenomena related to subjectivity, in the context of adopting instrumentality as a criterion of truth. This paper aims to discuss uses of the concept of private events from the standpoint of Pragmatism, a philosophy in which that criterion of truth has been consistently identified. It is particularly examined the focus on verbal relations in the analysis of contents related to privacy, and also how that focus reflects a rejection on mentalism and organicism. The paper continues to discuss the importance of the verbal community in the production of an individual “inside world”. In the end, the paper points out that some authors depart from functionalist/instrumentalist reference when working on the problem of imprecision of private events.